Brand Flexibility in Fashion: A Literature Review - Santoso, Fajar; Artha, Bhenu (Indo Publishing, 2025)
Fashion brands today face a rapidly evolving market environment where consumer expectations and competitive dynamics demand agility and innovation in branding strategies. Digital marketing adaptation has emerged as a cornerstone for achieving branding flexibility in the fashion industry. This article reviews current literature on how fashion brands implement branding flexibility through digital marketing strategies, drawing upon recent empirical studies, strategic frameworks, and case analyses from diverse markets. The review covers various digital marketing channels including social media, influencer partnerships, and artificial intelligence (AI) interventions, and highlights their role in shaping brand awareness and brand image. In this dynamic context, the ability to swiftly adapt branding strategies plays a pivotal role in the success and longevity of fashion brands.